Class II Division 1 malocclusion treatment with extraction of maxillary first molars: Evaluation of treatment and post‐treatment changes by the PAR Index. (1st September 2020) - Booij, Johan W.; Kuijpers‐Jagtman, Anne Marie; Bronkhorst, Ewald M.; Livas, Christos; Ren, Yijin; Kuijpers, Mette A.R.; Katsaros, Christos
Abstract: Objective: To investigate occlusal result and post‐treatment changes after orthodontic extraction of maxillary first permanent molars in patients with a Class II division 1 malocclusion. Setting and Sample: Retrospective longitudinal study in a private practice, with outcome evaluation by an independent academic hospital. Ninety‐six patients (53 males, 43 females) consecutively treated by one orthodontist with maxillary first permanent molar extraction were studied, divided into three facial types, based on pre‐treatment cephalometric values: hypodivergent (n = 18), normodivergent (n = 21) and hyperdivergent (n = 57). Methods: Occlusal outcome was scored on dental casts at T1 (pre‐treatment), T2 (post‐treatment) and T3 (mean follow‐up 2.5 ± 0.9 years) using the weighted Peer Assessment Rating (PAR) Index. The paired sample t test and one‐way ANOVA followed by Tukey's post hoc test were used for statistical analysis. Results: PAR was reduced by 95.7% and 89.9% at T2 and T3, respectively, compared with the start of treatment. The largest post‐treatment changes were found for overjet and buccal occlusion. Linear regression analysis did not reveal a clear effect (R‐Square 0.074) of age, sex, PAR score at T1, incremental PAR score T2‐T1, overjet and overbite at T1, and facial type on the changes after treatment (incremental PAR score T3‐T2). Conclusions: The occlusal outcome achieved after Class II division 1 treatment with maxillary first permanent molar extractions was maintained to a large extent over a mean post‐treatment follow‐up of 2.5 years. Limited changes after treatment were found, for which no risk factors could be discerned.